STRATEGI COPING STRES AKADEMIK MAHASISWA MELALUI TERAPI AL QUR'AN - Rival, Rival Agustina; Kholil, Kholil Lur Rochman (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Academic stress is one of the major challenges faced by students, especially during the completion of final assignments. Effective coping strategies are essential for maintaining mental health and improving academic performance. This study aims to explore the effectiveness of Qur'anic therapy as a form of spiritual coping in dealing with academic stress. The method used is a literature review with a descriptive qualitative approach. A total of 49 articles were identified and screened, resulting in 7 relevant articles for further analysis. The findings indicate that spiritual practices such as listening to Qur'anic recitation (murottal), engaging in dhikr, reading the Qur’an, and performing tahajjud prayer can help reduce anxiety, enhance inner peace, and strengthen students’ resilience. Qur'anic therapy serves as a means of spiritual reinforcement with a positive impact on emotional and psychological balance. This study concludes that Qur'anic therapy can be an alternative and practical approach to help students cope with academic pressure in a healthier and more meaningful way.